Falsafat Politik Wilāyah al-Faqīh - Husein Ja'far Al-Hadar (ILMU USHULUDDIN, 2014)
Relation between religion and state is an ultimate theme in the philosophy of Islamic politic. The theme has colored whole eminent Islamic philosophers, since al-Fārābī until Khomeini, and has given various concepts from Al-Madīna al-Fādila written by al-Fārābī to Khomeini’s Wilāya al-Faqīh. Actually, there are three views in the Islamic political philosophy. First, a secular concept, in which it has existed and found its reference after the Prophet’s era. Second, the concept undertakes religion in a limited way, in which the religion is adopted for morality corridor, and is used just to maintain the politic running within the moral ways. Third, integrality between religion and state, in which this becomes the very discussion in this article. The last thesis is proposed by Khomeini, who uses a terminology wilāya al-faqīh admitted by Iranian people through referendum 1979. By tracing the history of Islamic political philosophy, this writing will examine the concept of wilāya al-faqīh, from its conceptions till its implementation in the Republic of Iran.